Femininity in the field of abjection: The analysis of the position of the female subject in the phallogocentric framework of language and writing - Stojanović Dragana (Temida, 2014)
Using the platforms of psychoanalysis, theoretical psychoanalysis, poststructuralist studies and gender studies, this paper gives one possible aspect of analysis of the specificity of female position in phallogocentric framework of language and writing, which are the main elements that form and interpellate the gender positions of the subjects, as well as the phallogocentric-patriarchal dynamics between them. To understand the way in which the female subject is formed in this context is in the same time the first step towards the planning and performing the strategy of overcoming the borders that phallogocentric imposes on the subjects of language and writing, which is particularly seen in the case of the female subject and speaking position. The paper problematizes the terms as phallogocentric and abject, pointing towards women’s writing as of one of the possible strategies of resignification and alteration of phallogocentrism and its repressive mechanisms.